2006
DOI: 10.1007/s11060-005-9069-x
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of cerebral astrocytoma with 13N-ammonia

Abstract: There is a substantial uptake of 13N-ammonia in cerebral astrocytomas. 13N-ammonia PET may enable differentiation between low- and high-grade astrocytomas, and has the potential to enable differentiation between low-grade astrocytomas and non-neoplastic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…However, the accuracy of 18 F-FDG PET in identifying recurrence post-radiotherapy has been questioned by other studies [11,12]. For that reason, other positron-emitting radiotracers, such as 11 C-methionine and 13 N-ammonia, are under investigation, with encouraging results [13,14]. Even so, PET still remains relatively expensive and not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy of 18 F-FDG PET in identifying recurrence post-radiotherapy has been questioned by other studies [11,12]. For that reason, other positron-emitting radiotracers, such as 11 C-methionine and 13 N-ammonia, are under investigation, with encouraging results [13,14]. Even so, PET still remains relatively expensive and not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…The 13 N-NH 3 extraction of brain tissues depends primarily upon cerebral blood perfusion, capillary permeability-surface product (PS), and integrity of the glutamate-glutamine synthetase reaction [5]. Xiangsong et al [6,7] have reported that there is a substantial uptake of 13 N-NH 3 in cerebral astrocytomas, and that 13 N-NH 3 is a potential selective contrast-enhanced tracer for brain tumors, and may prove especially useful for evaluating the contrast-enhancing lesions on MRI to distinguish brain tumors from non-neoplastic lesions. In this study, we accordingly investigated the usefulness of 13 N-NH 3 PET for the evaluation of brain lesions that are hypometabolic on 18 F-FDG PET.…”
mentioning
confidence: 99%
“…As 13 N-ammonia is a perfusion tracer, it can be used for detecting recurrent tumours. Although 13 N-ammonia PET/computed tomography (CT) is routinely used for imaging myocardial perfusion, its role in imaging brain tumours is less clear [12,13]. The purpose of the study was to assess the value of 13 N-ammonia PET/CT in detecting recurrent gliomas and its ability to exclude radiation necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Overall sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 13 N-ammonia PET/CT were 82.6, 86.2, 82.6, 86.2 and 84.6%, respectively, whereas those of CE MRI were 96.7, 48.3, 59.5, 93.3 and 69.2%, respectively. Overall,13 N-ammonia PET/CT was statistically superior to CE MRI (P = 0.001). In low-grade tumours, 13 N-ammonia PET/CT performed better than MRI with an accuracy of 86.8 versus 68.4% (P = 0.003).…”
mentioning
confidence: 96%